(untitled) (International Journal of Engineering and Computer Science, 2014)
Experiments have been conducted to study the effect of addition of fly ash, copper slag, silica fume together with/without steel fibres or/and polypropylene fibres on 28-day compressive strength of concrete. While fly ash and copper slag are used for partial replacement of cement and fine aggregate respectively, defined quantity of steel fibres or/and polypropylene fibres were simply added to the mix proportions considered for the study. It is found from the experimental study that, in general, irrespective of the presence or absence of fibres, (i) for a given copper slag-fine aggregate ratio, increase in fly ash-cement ratio decreases 28-day compressive strength of the concrete and, the rate of decrease in the 28-day strength decrease with increase in copper slag-sand ratio (ii) for a given fly ash-cement ratio, increase in copper slag-fine aggregate ratio increases 28-day compressive strength of the concrete. Approximate equation is proposed to determine the 28-day compressive strength of the concrete containing fly ash, copper slag, silica fume and fibres.